Mudéjares granadinos y fiscalidad: los servicios extraordinarios de 1495 y 1499 - López de Coca Castañer, José Enrique (En la España Medieval, 2007)
The history of the Mudejar taxes of 1495 and 1499. The monarchs’ right to request them and Muslim chronclers’ points of view. The plan to distribute the first extraordinary tax and its modification. The opinion of fray Hernando de Talavera, archbishop of Granada. Problems collecting this tax: management of the comendador of Moratalla; resistance of the administrators of noble lordships; complaints and protests of taxpayers. The tax of 1499 and the “generosity” of notable Mudejars.